2020
DOI: 10.3390/ijerph17207523
|View full text |Cite
|
Sign up to set email alerts
|

Health-Care Services as a Platform for Building Community Resilience among Minority Communities: An Israeli Pilot Study during the COVID-19 Outbreak

Abstract: Background: Previous studies of minority groups in times of emergency have tended to focus on risk reduction or on individual resilience, overlooking the community factors that could be bolstered to promote better health and safety outcomes. The current study aimed to examine the role of health-care services in the perceived community resilience of urban and suburban Arab communities in Israel during the COVID-19 outbreak. Method: The study included 196 adults age 17–76 years, who filled out on-line questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 76 publications
0
6
0
1
Order By: Relevance
“…For example, Arab minority communities in Israel showed lower infection rates, which was (hypothetically) connected to younger age, social media use (in comparison to ultra-Orthodox Jewish communities that more often deter from social media use), cooperation between community leaders and governmental bodies, and distribution of medical knowledge due to the higher percentage of medically trained people in the community ( Saban et al, 2020 ). Other studies on the Arab community in Israel showed a picture consistent with effects seen in other minority groups: higher psychological distress, less resilience ( Kimhi et al, 2020 ) but more confidence in the medical and healthcare systems, especially in suburban communities than in urban communities ( Cohen et al, 2020 ). Overall, national identity struggles, discrimination, and social inequality in ethnic minority groups in Israel ( Slobodin and Cohen, 2020 ) and Arabic countries ( Kira et al, 2021 ) were exacerbated in the pandemic.…”
Section: Resultsmentioning
confidence: 52%
“…For example, Arab minority communities in Israel showed lower infection rates, which was (hypothetically) connected to younger age, social media use (in comparison to ultra-Orthodox Jewish communities that more often deter from social media use), cooperation between community leaders and governmental bodies, and distribution of medical knowledge due to the higher percentage of medically trained people in the community ( Saban et al, 2020 ). Other studies on the Arab community in Israel showed a picture consistent with effects seen in other minority groups: higher psychological distress, less resilience ( Kimhi et al, 2020 ) but more confidence in the medical and healthcare systems, especially in suburban communities than in urban communities ( Cohen et al, 2020 ). Overall, national identity struggles, discrimination, and social inequality in ethnic minority groups in Israel ( Slobodin and Cohen, 2020 ) and Arabic countries ( Kira et al, 2021 ) were exacerbated in the pandemic.…”
Section: Resultsmentioning
confidence: 52%
“…Seemingly, the role of trait resilience in coping with the pandemic's threats is even more fundamental compared with terror or natural disaster threats (Kimhi et al, 2020b). The COVID‐19 pandemic introduced a ‘ vuja‐de ’ phenomenon (Weick, 1993, p. 633), namely a phenomenon of sensemaking collapse, where nursing students sense that the world as they know it will never be the same again (Cohen et al, 2020; Hayter & Jackson, 2020). Namely, in an ambiguous reality where rules and conditions change daily, one cannot rely on leaders' instructions and solutions as those also keep changing according to the emerging circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of virus transmission during the pandemic is not solely dependent on the number of infected people; it also considers how vulnerable people and communities are in all facets of life, which can lead to losses and damages. Various studies have indicated that the susceptibility to COVID-19-related vulnerabilities is influenced by overt factors such as food scarcity because of income loss (Atmaja, Kusyati & Fukushi 2021 ; Mejia, Bhattacharya & Miraglia 2020 ), unsanitary living conditions, lack of water and hygiene facilities (Franco et al 2020 ; Jamieson & Van Blerk 2021 ; Kimani et al 2021 ) and inadequate healthcare resources (Caruso, Mela & Pede 2020 ; Cohen et al 2020 ). In addition, indirect factors contributing to vulnerability during the pandemic encompass population density (Batabyal & McCollum 2023 ), erosion of governance trust (Maudrie et al 2021 ; Wan 2021 ) and the COVID-19 stigma (Leach et al 2020 ).…”
Section: Response To Community Vulnerability During Covid-19mentioning
confidence: 99%